GEL TIME STUDIES IN ACTIVATION OF POLYESTER RESIN - BALASUBRAMANYAN, R (Fishery Technology, 2025)
GeUing times of po~yester resins with varying quantities ofcatalyst and accelerator were studied and the resuHs !reported inthis communication.